Diagnostic Value of Serum Cancer Antigen 125, Carcinoembryonic Antigen, Cancer Antigen 19-9, Anti Müllerian Hormone, White Blood Cell Count, Platelet Count, and Neutrophil to Lymphocyte Ratio in Endometriosis: A Retrospective Study - Behnaz Nouri; Niki Talebian; Ladan Kharaz; Mahdi Falah Tafti (International Journal of Fertility and Sterility)
Background: Endometriosis is among the leading causes of morbidity in the female population worldwide. Currently, the definite diagnosis of endometriosis depends on laparoscopy as the gold-standard method. Potential biomarkers, such as inflammatory biomarkers, cancer antigens, and hormones, offer non-invasive alternatives. This study was designed to investigate the utility of some hematological markers, including white blood cell (WBC) count, neutrophil to lymphocyte ratio (NLR), platelet count, cancer antigen 19-9 (CA 19-9), and 125 (CA-125), carcinoembryonic antigen (CEA), and anti Müllerian hormone (AMH), as non-invasive methods for endometriosis diagnosis.Materials and Methods: In this retrospective study, which was performed on 346 females, the case group consisted of 230 endometriosis patients. The data of 116 patients with benign tumors or other benign conditions such as Müllerian anomalies, were used as the control group. Receiver-operating characteristic (ROC) analysis was implemented to calculate specificities and sensitivities of CA-125, CA 19-9, CEA, NLR, WBC count, platelet (PLT) count, and AMH.Results: Significantly higher mean values were observed for CA-125, CA 19-9, WBC count, and NLR in the case group compared with the control group (P<0.001). The combination of NLR and CA-125 demonstrated the highest diagnostic performance with an area under the curve (AUC) of 0.903. However, the AUC for CA-125 (0.896) was lower and the value of 12.7 IU/mL was the most appropriate cut-off point (sensitivity=93.9%, specificity=60.9%). The cut-off value of 35 for CA-125 was also evaluated (sensitivity=61.4%, specificity=98.3%). The AUC for NLR was 0.699 and the best cut-off point was 1.5 (sensitivity=83.4%, specificity=52.6%).Conclusion: Combined measurement of CA-125 and NLR showed the highest performance in the diagnosis of endometriosis and can be considered as a diagnostic marker. However, it is necessary to conduct more research to evaluate the applicability of these biomarkers.